Thyroid-associated ophthalmopathy: Using diffusion tensor imaging to evaluate visual pathway microstructural changes - Li, Rui; Li, Jing; Wang, Zhenchang (Frontiers in Neurology, 2022)
objective: The aim of this study was to determine whether the visual pathway is affected by thyroid associated ophthalmopathy (TAO) before the development of dysthyroid optic neuropathy (DON) with diffusion tensor imaging (DTI). Material and Methods: Fifty-seven TAO patients (22 mild, 35 moderate-severe TAO) and 30 healthy controls (HCs) were included. The DTI parameters of the lateral geniculate (LG) and optic radiation (OR) were measured. A full ophthalmic examination including intraocular pressure, exophthalmos, and visual acuity was performed. Clinical activity scores (CAS) were also calculated. One-way ANOVA and Pearson’s correlation were carried out. A binary logistic regression was used to identify variables that can diagnose TAO. Results: Moderate-severe TAO patients showed significantly lower fractional anisotropy (FA) and higher mean diffusivity (MD) than HCs for both LG and OR (p < 0.05). FA of OR was negatively correlated with CAS and intraocular pressure. (P > 0.05). Multivariate analysis showed that FA of LG and FA of OR were significant predictor for diagnosis TAO. Conclusion: DTI parameters of the visual pathway were significantly altered in moderate-severe TAO patients. The FA of LG, in particular, can be used as a sensitive imaging biomarker for assessing subclinical visual pathway damage in TAO.